STRATEGI GURU DALAM MENGOPTIMALKAN MEDIA POWERPOINT UNTUK MENINGKATKAN MOTIVASI DAN PEMAHAMAN SISWA: STUDI KASUS DI SMP NEGERI 1 SINUNUKAN - Alma’rifatul Aisyah (Yayasan Baitul Hikmah al-Zain, 2026)
This study aims to improve students' motivation and understanding in Islamic Religious Education (PAI) learning through the use of PowerPoint media. The problem identified was the low student interest caused by conventional, non-visual teaching methods. This research used a Classroom Action Research (CAR) approach with the Kemmis and McTaggart model conducted in two cycles. The subjects were 28 seventh-grade students of SMP Negeri 1 Sinunukan. Data were collected through observation, interviews, questionnaires, and documentation, and analyzed using qualitative descriptive methods. The results showed an increase in student engagement and motivation after the application of interactive PowerPoint media. In the first cycle, only 57% of students met the minimum passing criteria, which increased to 85% in the second cycle. Students also became more active in discussions and reported that the lessons were more engaging and easier to understand. The conclusion is that systematic and interactive use of PowerPoint is effective in enhancing the quality of PAI learning, both in terms of students' understanding and enthusiasm.